The Student Responses of Teacher Questioning Probing Strategies to Promote The Student Critical Thinking in Classroom Interaction - Lestari, Dela Rosita (RETAIN, 2022)
Abstract The purpose of this study was to determine whether probing strategies can develop the students' critical thinking. This qualitative research uses a discourse analysis approach. The subject of this research is the students of X grade at SMA Paciran. Data collection was carried out through recording, observations, questionnaires, and interviews. The collected data were analyzed through questionnaires and conversational analysis of the probing strategy and student responses to probing questioning strategies that were implemented by the teacher. The results showed that the probing strategy can support the students' critical thinking. Keywords: Probing Questioning Strategies, Critical Thinking, Students Responses.